Child safeguarding in a peacekeeping context: lessons from Liberia. Issue 6 (18th August 2019) - Blakemore, Sarah; Freedman, Rosa; Lemay-Hébert, Nicolas
ABSTRACT: This article reviews how peacekeeping officials safeguard children from sexual exploitation and abuse (SEA) in Liberia, more than 15 years after the landmark reports published on this issue. Based on original fieldwork conducted in Liberia and in New York, the article introduces an innovative framework to assess whether or not organisations effectively safeguard children from SEA. It reviews three interrelated issues: reinforcing the institutional environment in the country, strengthening prevention of and accountability for child SEA by UN actors. The article concludes with specific policy recommendations for actors involved in peacekeeping activities.